Understanding the structural basis of substrate recognition by Plasmodium falciparum plasmepsin V to aid in the design of potent inhibitors - Bedi, Rajiv K. (Sci Rep, 2016)
Plasmodium falciparum plasmepsin V (PfPMV) is an essential aspartic protease required for parasite survival, thus, considered as a potential drug target. This study reports the first detailed structural analysis and molecular dynamics simulation of PfPMV as an apoenzyme and its complexes with the substrate PEXEL as well as with the inhibitor saquinavir. The presence of pro-peptide in PfPMV may not structurally hinder the formation of a functionally competent catalytic active site. The structure of PfPMV-PEXEL complex shows that the unique positions of Glu179 and Gln222 are responsible for providing the specificity of PEXEL substrate with arginine at P3 position. The structural analysis also reveals that the S4 binding pocket in PfPMV is occupied by Ile94, Ala98, Phe370 and Tyr472, and therefore, does not allow binding of pepstatin, a potent inhibitor of most pepsin-like aspartic proteases. Among the screened inhibitors, the HIV-1 protease inhibitors and KNI compounds have higher binding affinities for PfPMV with saquinavir having the highest value. The presence of a flexible group at P2 and a bulky hydrophobic group at P3 position of the inhibitor is preferred in the PfPMV substrate binding pocket. Results from the present study will aid in the design of potent inhibitors of PMV.